Portuguese recommendations for the use of biological therapies in patients with rheumatoid arthritis -2016 update - Duarte, Cátia (2018)
Objective: To update the recommendations for the treatment of rheumatoid arthritis (RA) with biological therapies, endorsed by the Portuguese Society of Rheu -matology (SPR). Methods: These treatment recommendations were formulated by Portuguese rheumatologists based on litera -ture evidence and consensus opinion. At a national meeting the 11 recommendations were discussed and updated. The document resulting from this meeting circulated to all Portuguese rheumatologists, who anonymously voted online on the level of agreement with the recommendations. Results: These recommendations cover general aspects as shared decision, prospective registry in Reuma.pt, asses sment of activity and RA impact and treatment objec tive. Consensus was also achieved regarding specific aspects as initiation of biologic therapy, assessment of res pon se, switching and definition of persistent remission. Conclusion: These recommendations may be used for guidance of treatment with biological therapies in patients with RA. As more evidence becomes available and more therapies are licensed, these recommendations will be updated.